SOCIAL CULTURAL ISSUES AND PROBLEMS IN MI/SD SERANG : SOCIAL STUDIES LEARNING - Muhammad Farizul Umam (JELIM : Journal of Education, Language, Social and Management, 2023)
The aim of this study is to dig into the trend of globalization, cultural diversity, environmental issues, legal awareness of citizens, cultural pluralism and ethnic diversity in elementary school social science. This method of study belongs to a descriptive analysis study using the method for library research to study and address the issues and social issues of elementary school learning cultures. The data-gathering techniques in this study by locating and gathering data that support the cultural issues and problems of elementary school children's social sciences, both from books and journals. Thereafter, the data obtained was analyzed in order to achieve what was achieved intact and to draw conclusions and answer rules. The result of this study is first, the trend of globalization and the diversity of cultures in Indonesia became the central subject of IPS education regarding issues that people face in the social order of life. Second, environmental issues become the most influential IPS study subjects. Third, citizen legal awareness is appropriate to consider with regard to the application of the law in the lives of citizens especially for trainees who can be accepted as applying it in IPS study. Fourth, cultural pluralism and ethnic diversity are discussions of cultural issues and issues that often arise in society even in small spheres by learners in classes or schools.